Barrels XXXI comes to the inland empire. (2nd January 2019) - Barrientos, Alicia C.; Cataldo, Giuseppe; Brumberg, Joshua C.
Abstract: The 31st annual Barrels meeting was held on the campus of the University of California, Riverside on the first two days of November, 2018. The meeting focuses on the whisker to cortical barrel pathway and the systems it impacts. This year's meeting focussed on the neural mechanisms of motor control, the functions of higher order thalamic nuclei and adaptable perception and decision-making.